HUBUNGAN PENGETAHUAN DAN SIKAP, DENGAN TINDAKAN PETUGAS KESEHATAN DALAM PENGELOLAAN LIMBAH MEDIS DI PUSKESMAS TANJUNG AGUNG KABUPATEN OGAN KOMERING ULU - Chandra, Elwan; Sarwoko, Sabtian (Jurnal Kesehatan dan Pembangunan, 2025)
Health service places, one of which is the Community Health Center, are one of the public service facilities that do not rule out the possibility of causing environmental pollution and can be a medium for the spread of various diseases. This study aims to determine the Relationship between Knowledge and Attitudes with the Actions of Health Workers in Medical Waste Management at the Tanjung Agug Community Health Center, Ogan Komering Ulu Regency. This study uses an analytical survey method with a cross-sectional approach. Data analysis uses univariate and bivariate analysis with the chi square test. The sample in the study was Health Workers at the Tanjung Agung Community Health Center, totaling 108 people. Based on univariate analysis, there were 85 respondents (78.7%) of health workers with good actions, there were 78 (72.2%) of health workers with good knowledge, there were 73 (67.6%) of health workers with positive attitudes, there were 77 (71.3%) There is a relationship between knowledge and actions of health workers with P-Value 0.07, attitudes and actions of health workers with P-Value 0.011, The conclusion of this study is that there is a significant relationship between knowledge and attitudes in medical waste management at the Tanjung Agung Health Center, Ogan Komering Ulu Regency, suggestions to the health center to provide training, seminars to health workers in medical waste management.